Multiple Origins and Specific Evolution of CRISPR/Cas9 Systems in Minimal Bacteria (Mollicutes) - Ipoutcha, Thomas; Tsarmpopoulos, Iason; Talenton, Vincent; Gaspin, Christine; Moisan, Annick; Walker, Caray A.; Brownlie, Joe; Blanchard, Alain; Thebault, Patricia; Sirand-Pugnet, Pascal (Frontiers in Microbiology, 2019)
CRISPR/Cas systems provide adaptive defense mechanisms against invading nucleic acids in prokaryotes. Because of its interest as a genetic tool, the Type II CRISPR/Cas9 system from Streptococcus pyogenes has been extensively studied. It includes the Cas9 endonuclease that is dependent on a dual-guide RNA made of a tracrRNA and a crRNA. Target recognition relies on crRNA annealing and the presence of a protospacer adjacent motif (PAM). Mollicutes are currently the bacteria with the smallest genome in which CRISPR/Cas systems have been reported. Many of them are pathogenic to humans and animals specifically, mycoplasmas, and plants specifically, phytoplasmas and some spiroplasmas. A global survey was conducted to identify and compare CRISPR/Cas systems found in the genome of these minimal bacteria. Complete or degraded systems classified as Type II-A and less frequently as Type II-C were found in the genome of 21 out of 52 representative mollicutes species. Phylogenetic reconstructions predicted a common origin of all CRISPR/Cas systems of mycoplasmas and at least two origins were suggested for spiroplasmas systems. Cas9 in mollicutes were structurally related to the S. aureus Cas9 except the PI domain involved in the interaction with the PAM, suggesting various PAM might be recognized by Cas9 of different mollicutes. Structure of the predicted crRNA/tracrRNA hybrids was conserved and showed typical stem-loop structures pairing the Direct Repeat part of crRNAs with the 5’ region of tracRNAs. Most mollicutes crRNA/tracrRNAs showed G+C% significantly higher than the genome, suggesting a selective pressure for maintaining stability of these secondary structures. Examples of CRISPR spacers matching with mollicutes phages were found, including the textbook case of Mycoplasma cynos strain C142 having no prophage sequence but a CRISPR/Cas system with spacers targeting prophage sequences that were found in the genome of another M. cynos strain that is devoid of a CRISPR system. Despite their small genome size, mollicutes have maintained protective means against invading DNAs, including restriction/modification and CRISPR/Cas systems. The apparent lack of CRISPR/Cas systems in several groups of species including main pathogens of humans, ruminants and plants suggests different evolutionary routes or a lower risk of phage infection in specific ecological niches.